Changes in adiposity among children and adolescents in the United States, 1999–2006 to 2011–2018. Issue 4 (22nd July 2021) - Stierman, Bryan; Ogden, Cynthia L; Yanovski, Jack A; Martin, Crescent B; Sarafrazi, Neda; Hales, Craig M
ABSTRACT: Background: Data from the NHANES indicate that BMI has increased in some subgroups of children and adolescents in the United States over the past 20 y; however, BMI is an indirect measure of body fatness. Objectives: We assessed changes in DXA-derived measures of adiposity in a nationally representative population of US children and adolescents aged 8–19 y from 1999–2006 to 2011–2018. Methods: Using data from the NHANES, we compared the means and distributions of DXA-derived percentage body fat (%BF) and fat mass index (FMI; fat mass/height 2 in kg/m 2 ) between 1999–2006 ( n = 10, 231) and 2011–2018 ( n = 6923) among males and females by age group, race and Hispanic origin, and BMI categories. Estimates were standardized by age and race and Hispanic origin. Results: From 1999–2006 to 2011–2018, mean %BF increased from 25.6% to 26.3% (change in %BF: 0.7%; 95% CI: 0.2%, 1.2%; P < 0.01) among all males, whereas mean %BF increased from 33.0% to 33.7% (change in %BF: 0.7%; 95% CI: 0.2%, 1.2%; P = 0.01) and mean FMI increased from 7.7 to 8.0 fat mass kg/m 2 (change in FMI: 0.3 fat mass kg/m 2 ; 95% CI: 0.0, 0.6 fat mass kg/m 2 ; P = 0.02) among all females. Changes were not consistent across all age, race and Hispanic origin, and BMI categories. Both %BF and FMI increased among Mexican-American children and adolescents, but not other race and Hispanic origin groups. Conclusions: Among US children and adolescents, DXA-derived measures of adiposity increased from 1999–2006 to 2011–2018, albeit not consistently in every age, race and Hispanic origin, and BMI subgroup. These data reinforce the need to consider other measures, besides BMI categories, when studying adiposity in children and adolescents.